2000
DOI: 10.1103/physrevd.62.016010
|View full text |Cite
|
Sign up to set email alerts
|

D-term spectroscopy in realistic heterotic-string models

Abstract: The recent emergence of free fermionic heterotic string models with solely the MSSM charged spectrum below the string scale reinforces the motivation to investigate the pheneomelogical characteristics of this class of string models, which possess an underlying Z 2 ϫZ 2 orbifold structure. An important property of the Z 2 ϫZ 2 orbifold is the cyclic permutation symmetry between the three twisted sectors. If preserved in the three-generation models the cyclic permutation symmetry results in a family universal an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…Low scale supersymmetry is therefore not a necessary outcome of string theory, but certainly its observation will provide further evidence that the different structures of string constructions are realised in nature. Specific SUSY breaking scenarios in string models give rise to distinct supersymmetric spectra and that in turn will be used to constrain further the phenomenological string vacua [95]. It is further noted that R-parity is generically broken in string vacua [96] and that the LSP is not expected therefore to provide a viable dark matter candidate.…”
Section: Toward String Predictionsmentioning
confidence: 99%
“…Low scale supersymmetry is therefore not a necessary outcome of string theory, but certainly its observation will provide further evidence that the different structures of string constructions are realised in nature. Specific SUSY breaking scenarios in string models give rise to distinct supersymmetric spectra and that in turn will be used to constrain further the phenomenological string vacua [95]. It is further noted that R-parity is generically broken in string vacua [96] and that the LSP is not expected therefore to provide a viable dark matter candidate.…”
Section: Toward String Predictionsmentioning
confidence: 99%
“…These studies are reviewed in [25], where further details can be found. These include among others: top quark mass prediction [31], several years prior to the actual observation by the CDF/D0 collaborations [37]; generations mass hierarchy [38]; CKM mixing [39]; superstring see-saw mechanism [40]; Gauge coupling unification [41]; Proton stability [42]; supersymmetry breaking and squark degeneracy [43,44]. Additionally, it was demonstrated in ref.…”
Section: Free Fermionic Model Buildingmentioning
confidence: 99%
“…The second issue we consider is the possibility of minima that break charge and colour lying along F and D flat directions [10,13,14,15,16,17,18]. The constraints found by requiring that there be no such (CCB) minima are dependent on the distance from the QFP.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we consider the empirically derived lower bound upon the lightest CP-even MSSM Higgs mass, which in the canonical GUT scenarios has been shown to be a strong restriction upon the QFP scenario [12]. The second issue we consider is the possibility of minima that break charge and colour lying along F and D flat directions [10,13,14,15,16,17,18]. The constraints found by requiring that there be no such (CCB) minima are dependent on the distance from the QFP.…”
mentioning
confidence: 99%